Bio-based poly(isobornyl acrylate)-b-(citronellyl methacrylate) block copolymers by PET-RAFT polymerization: thiol-ene modification and adhesion studies - Hetkale, Pragati M.; Purohit, Poorvi M.; Nair, Kiran Sukumaran; Ambade, Ashootosh V. (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2025)
In this study, poly(isobornyl acrylate)-b-poly(citronellyl methacrylate) (PIBA-b-PCMA) block copolymers were synthesized with controlled molecular weights and low dispersity using photoinduced electron transfer-reversible addition-fragmentation chain transfer (PET-RAFT) polymerization of isobornyl acrylate (IBA) and citronellyl methacrylate (CMA), both terpene-derived monomers. A series of block copolymers was obtained by varying the chain length of PCMA block. Kinetics study of the polymerization of IBA and CMA using 4-cyano-(((dodecylthio)carbonothioyl)thio)pentanoic acid (CDTPA) as chain transfer agent showed a linear plot of ln[M]0/[M]t vs time indicating first order reaction. Distinct glass transition temperatures were observed for the individual blocks and enhanced thermal stability was seen with increasing PCMA content. Post-polymerization modification of the polymer was demonstrated using thiol-ene reaction with the vinyl group in the pendent citronellyl moiety. Adhesion performance, evaluated through lap shear test on aluminum substrates, showed that the block copolymers achieved peak shear strengths of 1.74 MPa at a 38:62 PIBA:PCMA mole ratio.
Keywords: adhesion strength; Bio-based polymers; block copolymers; PET-RAFT polymerization; Thiol-ene reaction